2021
DOI: 10.1097/psn.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Performing Reconstructive Microsurgery on Patients With COVID-19

Abstract: On March 11, 2020, the World Health Organization declared COVID-19 to be a pandemic, challenging health care systems all over the world. National health care systems have reorganized to cope with the disease. Surgical services departments around the world have been affected and elective surgical procedures have been postponed to conserve medical resources. When a patient with COVID-19 requires an urgent microsurgical free flap due to trauma or a tumor, personnel from the health care facility must have a protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…More specifically, COVID‐19 has affected both elective and emergent surgery procedures, across all specialties (Collaborative CO, 2020a ; Moletta et al, 2020 ). From stringent personal protective equipment (PPE) protocols to pre‐admission and discharge screening measures which have frequently led to the postponement of procedures and increased length of hospital stay respectively, SARS‐CoV‐2 has truly altered surgical life as we knew it (Miller et al, 2020 ; Patel et al, 2020 ; Prasad et al, 2021 ; Thione et al, 2021 ; Toro et al, 2021 ; Yuan & Jiang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, COVID‐19 has affected both elective and emergent surgery procedures, across all specialties (Collaborative CO, 2020a ; Moletta et al, 2020 ). From stringent personal protective equipment (PPE) protocols to pre‐admission and discharge screening measures which have frequently led to the postponement of procedures and increased length of hospital stay respectively, SARS‐CoV‐2 has truly altered surgical life as we knew it (Miller et al, 2020 ; Patel et al, 2020 ; Prasad et al, 2021 ; Thione et al, 2021 ; Toro et al, 2021 ; Yuan & Jiang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many surgeons have devised innovative safety protocols to help these patients receive necessary procedures. [5][6][7] Studies have examined the effects of these altered protocols on patient course and complication rates, specifically in the context of microsurgical head and neck (HN) reconstruction. 8 Preliminary center-specific studies have demonstrated that, with adjusted safety protocols and careful patient selection, there has been significant difference in complications when these measures to mitigate viral exposure are taken.…”
Section: Accepted Manuscriptmentioning
confidence: 99%